Pathogenesis and treatment of multiple myeloma bone disease - Masahiro Hiasa; Takeshi Harada; Eiji Tanaka; Masahiro Abe (Elsevier, 2021)
Multiple myeloma (Plasma cell myeloma), a malignancy of the plasma cells, exhibits tumor expansion preferentially in the bone marrow and the development of bone-destructive lesions. Multiple myeloma is still an incurable disease with changes in the bone marrow microenvironment in favor of the survival and proliferation of multiple myeloma cells and bone destruction. In this review, we described the recent findings on the regulators involved in the development of myeloma bone diseases, and succinctly summarize currently available therapeutic options and the development of novel bone modifying agents for myeloma treatment.